1995
DOI: 10.1507/endocrj.42.265
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Specific Mutations in the Tyrosine Kinase Domain of the RET Proto-Oncogene in Pheochromocytomas of Sporadic Type.

Abstract: Abstract.Sporadic pheochromocytomas, sporadic medullary thyroid carcinomas (MTCs), pheochromocytomas and/or MTCs in multiple endocrine neoplasia (MEN) 2A or 2B were screened for mutations in the tyrosine kinase domain of the RET proto-oncogene by direct sequencing of PCR-amplified products or sequencing subcloned DNAs from PCR-products. All tumors of 4 MEN 2B patients were confirmed to contain a heterozygous missense mutation at codon 918 (ATG-~ACG; Met-Thr) of the RET proto-oncogene as well as their leukocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Recently, we found codon 918 mutations in 31% of sporadic pheochromocytomas (cases 13-16 in Table 1 in this study), for which mutations were heterozygous and tumor-specific [9]. In this study, codon 768 mutations were shown to be rare in sporadic pheochromocytomas in contrast to sporadic MTCs.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Recently, we found codon 918 mutations in 31% of sporadic pheochromocytomas (cases 13-16 in Table 1 in this study), for which mutations were heterozygous and tumor-specific [9]. In this study, codon 768 mutations were shown to be rare in sporadic pheochromocytomas in contrast to sporadic MTCs.…”
Section: Discussionsupporting
confidence: 57%
“…With respect to sporadic pheochromocytomas, we detected codon 918 mutations in 31% of sporadic pheochromocytomas [9]. In the present study, we analyzed sporadic pheochromocytomas and pheochromocytomas with neurofibromatosis 1 (NF1), MEN 2A, or MEN 2B for mutations of codon 768 of the RET proto-oncogene.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The affected codons were cysteine at 634 (12 patients) and tyrosine at 791 (one patient), both of which are associated with MEN 2A/FMTC development, and most of the patients with RET germline mutations developed MTC during the follow-up period, indicating that clinically apparent sporadic pheochromocytomas associated with RET germline mutations might be part of undiagnosed MEN 2 [127]. Somatic RET mutations have also been detected in 0-31% of patients with sporadic pheochromocytoma, mostly at codon 918 [133][134][135].…”
Section: Sporadic Pheochromocytomamentioning
confidence: 99%
“…In sporadic MTCs and pheochromocytomas, codon 918 mutations were detected fre¬ quently (3,5,6), but mutations in the cysteine-rich region of the RET proto-oncogene were found to be rare (7,8). In sporadic MTCs and pheochromocytomas, codon 918 mutations were detected fre¬ quently (3,5,6), but mutations in the cysteine-rich region of the RET proto-oncogene were found to be rare (7,8).…”
mentioning
confidence: 99%